(Con)texte littéraire dans les manuels de français au niveau secondaire en Pologne - Chmiel-Bożek, Halina (Neofilolog, 2022)
Regardless of the teaching method, literature has always been an element of language learning. The action-oriented approach – proposed more than 20 years ago – does not exclude references to literature in the language classroom. The Companion Volume to the Common European Framework of Reference for Languages, published in 2021, further expands the possibilities for using literary texts in foreign language teaching methodology. This paper will analyse eighteen approved French textbooks from the point of view of the literature-based exercises they contain. The aim is to determine to what extent and with what regularity literature fragments appear in these textbooks and establish the types and objectives of literature-based exercises.